ADDITION OF SEAWEED FLOUR (Eucheuma cottonii) AS FIBER SOURCE AGAINST CENDOL LEVEL OF FLAVOR - Parliamentary, Fazira; Rostini, Iis; Nurruhwati, Isni; Pratama, Rusky Intan (Jurnal Perikanan Unram, 2025)
This study aims to determine the effect of adding Eucheuma cottonii seaweed flour on the chemical and organoleptic characteristics of cendol. This research was conducted at the Fisheries Products Processing Laboratory of the Faculty of Fisheries and Marine Sciences of Padjadjaran University, as well as at the SIG Laboratory (PT. Saraswanti Indo Genetech) Bogor. The research method used was an experimental method using 4 seaweeds concentration treatments of 0%, 5%, 10%, and 15%. A total of 25 semi-trained panelists were tested for organolpetic testing. The parameters include the degree of favorability, aroma, taste, and texture as well as the levels of water, protein, fat, ash, dietary fiber. Organoleptic test results data were analyzed with Friedman and Bayes tests, while chemical tests were analyzed in a comparative descriptive manner. The results of this study show that adding 5% Eucheuma cottonii seaweed flour to cendol is the most preferred treatment based on organoleptic parameters with an average likeness value (7,3); aroma (6,8); taste (7,0); and texture (6,8); and producing a proximate composition of water (91,55%), ash (0,16%); protein (0,59%); fat (0,02%); carbohydrate (7,70%); and dietary fiber (1,94%).